State, Anarchy, Collective Decisions - Coram, A. author. aut Link
XIII, 176 p.
Keywords: State, Anarchy and Collective Decisions provides an introduction to the applications of game theory to a series of questions that are fundamental in political economy. These questions include: Why do we need states? What might happen without protection for life and property? How might tribes or criminal gangs behave in struggles over material possessions? Would people tell the truth if asked what they wanted?